The AI Revolution in Health Literacy: Bridging the Knowledge Gap - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Keywords: Artificial Intelligence, Health Literacy, Digital Health, Patient Education, Health Communication, SEO Introduction: The Imperative of Health ...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Medical Ethics; Healthcare Data